Barriers to cycling : an exploration of quantitative analyses - Parkin, J; Ryley, T; Jones, T (Ashgate, 2007)
This book chapter is from Cycling and society: How can the social sciences help us to understand the past, present and potential futures of cycling? This timely international and interdisciplinary collection addresses this question, discussing shifts in cycling practices and attitudes, and opening up important critical spaces for thinking about the prospects for cycling. The book brings together, for the first time, analyses of cycling from a wide range of disciplinary backgrounds, including history, sociology, geography, planning, engineering and technology. The book redresses the past neglect of cycling as a topic for sustained analysis by treating it as a varied and complex practice which matters greatly to contemporary social, cultural and political theory and action. Cycling and Society demonstrates the incredible diversity of contemporary cycling, both within and across cultures. With cycling increasingly promoted as a solution to numerous social problems across a wide range of policy areas in car-dominated societies, this book helps to open up a new field of cycling studies.